Leaching behavior of pollutants in ferrochrome arc furnace dust and its stabilization/solidification using ferrous sulphate and Portland cement - Bulut, Ulkue; Ozverdi, Arzu; Erdem, Mehmet (Elsevier, 2009)
In this study, dissolution properties under different conditions and pollution potential by toxicity characteristic leaching procedure (TCLP) of arc furnace dust generated in the production of ferrochrome were examined and some stabilization/solidification (S/S) techniques were applied to the dust depending on contaminants determined. Dissolution properties and pollution potentials of all the materials stabilized/solidified were also studied under the similar conditions. It was determined that the metallic components concentrations dissolved from the ferrochrome arc furnace dust (FAFD) except for chromium and zinc were below the detection limits. The chromium concentration dissolved from the FAFD by TCLP was found to be 9.8 mg/l. Portland cement (PC), PC-FeSO4 and PC-sand-FeSO4 mixtures for S/S of the FAFD were tested. Although metal ions in the cationic form were stabilized when the PC was only used, Cr(VI) in the sample was not changed depending on PC amount and remained in the soluble chromate form. The stabilization efficiency of Cr(VI) increased by the increasing amounts of PC and FeSO4. The best S/S of the FAFD was accomplished when the 5 stoichiometric amounts of FeSO4, 30% PC and 16% sand mixture were used. TCLP leaching results of the samples obtained under the optimum conditions were below the EPA landfilling limits. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Arc furnace dust; Chromium; Stabilization; Solidification